Electrocortical changes associated with minocycline treatment in fragile X syndrome. (October 2013) - Schneider, Andrea; Leigh, Mary Jacena; Adams, Patrick; Nanakul, Rawi; Chechi, Tasleem; Olichney, John; Hagerman, Randi; Hessl, David
Minocycline normalizes synaptic connections and behavior in the knockout mouse model of fragile X syndrome (FXS). Human-targeted treatment trials with minocycline have shown benefits in behavioral measures and parent reports. Event-related potentials (ERPs) may provide a sensitive method of monitoring treatment response and changes in coordinated brain activity. Measurement of electrocortical changes due to minocycline was done in a double-blind, placebo-controlled crossover treatment trial in children with FXS. Children with FXS (Meanage 10.5 years) were randomized to minocycline or placebo treatment for 3 months then changed to the other treatment for 3 months. The minocycline dosage ranged from 25–100 mg daily, based on weight. Twelve individuals with FXS (eight male, four female) completed ERP studies using a passive auditory oddball paradigm. Current source density (CSD) and ERP analysis at baseline showed high-amplitude, long-latency components over temporal regions. After 3 months of treatment with minocycline, the temporal N1 and P2 amplitudes were significantly reduced compared with placebo. There was a significant amplitude increase of the central P2 component on minocycline. Electrocortical habituation to auditory stimuli improved with minocycline treatment. Our study demonstrated improvements of the ERP in children with FXS treated with minocycline, and the potential feasibility and sensitivity of ERPs as a cognitive biomarker in FXS treatment trials.